Allometric Ratio of Menthol and Menthone to Pulegone in the Essential Oil of Peppermint (Mentha piperita L.) Affected by Bioregulators - Meisam Pourhadi; Hassanali Naghdi Badi; Ali Mehrafarin*; Heshmat Omidi; Reza Hajiaghaee (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Menthol and menthone are two important components in the essential oil of peppermint(Mentha piperita L.) which are commercially used in the pharmaceutical industries. This study has presented the allometric ratio of menthol and menthone to pulegone affected by the induction of bioregulators. Methods: The experiment was conducted in controlled condition based on completely randomized design (CRD) in three replications. The plants were subjected to different bioregulator treatments including distilled water; 5 %v/v methanol; 40 ppm GA3 (gibberellic acid) + 5%v/v methanol; 40 ppm IBA (indole butyric acid) + 5%v/v methanol, and 40 ppm GA3 + 40 ppm IBA + 5%v/v methanol. Essential oils analysis were performed using different methods of gas chromatography and gas chromatography-mass spectroscopy. Results: The application of 40 ppm IBA + 5%v/v methanol increased the essential oil content. With the use of bioregulators, the content of menthol and menthone increased and the amount of pulegone was conversely reduced. The lowest content of pulegone was measured in the treatment with 40 ppm GA3 + 40 ppm IBA + 5%v/v methanol. Allometric analysis of components showed that the ratios of menthol/pulegone, menthone/pulegone, and (menthone+menthol)/pulegone increased by bioregulators application, especially with 40 ppm GA3 +  40 ppm IBA + 5%v/v  methanol. Conclusion: Using plant bioregulators could be a suitable procedure to increase pro-health potential through increasing the amount of menthol with decreasing the content of pulegone in the essential oil. It is possible that the bioregulators were able to convert pulegone to menthol and menthone.